Effect of Fe–Mo–Cr pre-alloyed powder on the microstructure and mechanical properties of TiC–high-Mn-steel cermet. (November 2019) - Li, Guoping; Yang, Hao; Lyu, Yinghai; Zhou, Haojun; Luo, Fenghua
Abstract: In the study, a TiC–high-Mn-steel cermet is fabricated using FeMo and Fe–Mo–Cr pre-alloyed powders as metallic binders by powder metallurgy techniques. The effect of Cr on the microstructure and mechanical properties of the cermet is studied and the cermet preparation process is optimized. The microstructure and fracture morphology of the cermets are observed with scanning electron microscopy, while phase identification and analysis are performed by X-ray diffractometry. The results show that the particles of Cr-free cermet are angular and polygonal, while those of cermet with added Cr are rounded and ellipsoidal. The grains of Cr-free cermet are larger than those of the Cr-added cermet, which is unlike similar conventional cermets. The grain size of the Cr-added cermet increases slightly with increased Cr content. In addition, the relative density of the cermet decreases slightly with increased Cr content. The hardness of cermet is maximized at HRC 64.8 with the Cr content of 1.0 wt%; with further increases in Cr, the hardness decreases gradually. The transverse rupture strength and impact toughness first increase and then decrease with increasing Cr content, reaching the maxima of 2355 MPa and 13.42 J/cm 2, respectively, at the Cr content of 1.5 wt%. The strength and toughness of the cermet are improved greatly compared to those of conventional similar TiC–high-Mn-steel cermets. Highlights: Fe–Mo–Cr pre-alloyed powder is used in forming TiC–high-Mn-steel cermets. Cr composition is varied by manipulating pre-alloyed powder ratios. Pre-alloyed powder changes cermet behavior via particle size variations. Produced cermets have core–rim morphologies similar to conventional cermets. Cr-added cermets show smaller grains, higher strength, and higher impact toughness.